Industry- and occupation-specific human capital: evidence from displaced workers - Lagoa, S. (2017)
Purpose - The purpose of this paper is to estimate the impact of industry and occupation skills on the wages of displaced workers due to firm closure. Design/methodology/approach - Using linked employer-employee data on displaced workers, this paper estimates the impact of industry and occupation tenure on post-displacement wage changes correcting for endogeneity with a multinomial logit model. Findings - The evidence suggests that occupation has more specific skill requirements than industry. Displaced workers moving both industry and occupation suffer a higher wage decline than those changing only industry or occupation. Furthermore, the transferability of skills varies across occupations and industries; more specifically, intermediate-level occupations are more demanding in specific skills and impose higher wages losses for displaced workers. Finally, the economic crisis reduced the return on firm-specific skills only in some cases. Practical implications - The examination of skill specificity/transferability helps firms, workers and policy makers to draw strategies and policies to improve their individual situation and social welfare. The analysis suggest that when experienced workers are displaced and forced to find a job in a different industry, they suffer considerable wage cuts. While displacement imposes costs to workers and society, different choices impact wages differently. Originality/value - To the authors' best knowledge, this is the first paper studying the simultaneous impact of industry and occupation tenure on wages using displaced workers due to firm closing. The paper also corrects for the selection of different alternatives after the displacement and uses data from a country characterised by low-job flows and low-worker flows. Finally, the impact of economic crises on return to skills is assessed.